c-Fos Protects Neurons Through a Noncanonical Mechanism Involving HDAC3 Interaction: Identification of a 21-Amino Acid Fragment with Neuroprotective Activity - Rawat, Varun (Mol Neurobiol, 2015)
Proteins belonging to the AP-1 family of transcription factors are known to be involved in the regulation of neuronal viability. While strides have been made to elucidate the mechanisms of how individual members regulate cell death, much remains unknown. We find that the expression of one AP-1 member, c-Fos, is reduced in cerebellar granule neurons (CGNs) induced to die by low potassium (LK) treatment. Restoration and increase of this expression protect CGNs against LK-induced death, whereas knockdown induces death of otherwise healthy neurons. Furthermore, forced expression can protect cortical neurons against homocysteic acid (HCA)-induced toxicity. Taken together, this suggests that c-Fos is necessary for neuronal survival and that elevating c-Fos expression has a neuroprotective effect. Consistent with this idea is the finding that c-Fos expression is reduced selectively in the striatum in two separate mouse models of Huntington’s disease and forced expression protects against neuronal death resulting from mutant huntingtin (mut-Htt) expression. Interestingly, neuroprotection by c-Fos does not require its DNA-binding, transcriptional, or heteromerization domains. However, this protective activity can be inhibited by pharmacological inhibition of c-Abl, CK-I, and MEK-ERK signaling. Additionally, expression of point mutant forms of this protein has identified that mutation of a tyrosine residue, Tyr345, can convert c-Fos from neuroprotective to neurotoxic. We show that c-Fos interacts with histone deacetylase-3 (HDAC3), a protein that contributes to mut-Htt neurotoxicity and whose overexpression is sufficient to promote neuronal death. When co-expressed, c-Fos can protect against HDAC3 neurotoxicity. Finally, our study identifies a 21-amino acid region at the C-terminus of c-Fos that is sufficient to protect neurons against death induced by LK, HCA treatment, or mut-Htt expression when expressed via a plasmid transfection or as a cell-permeable peptide. This cell-permeable peptide, designated as Fos-CTF, could have potential as a therapeutic agent for neurodegenerative diseases.